A search for time dependent neutrino emission from microquasars with the ANTARES telescope - Adrián-Martínez, S.; Albert, A.; André, M.; Anghinolfi, M.; Anton, G.; Ardid, M.; Astraatmadja, T.; Aubert, J.; Baret, B.; Barrios, J.; Basa, S.; Bertin, V.; et al. (2014)
© 2014 Elsevier B.V. Results are presented on a search for neutrino emission from a sample of six microquasars, based on the data collected by the ANTARES neutrino telescope between 2007 and 2010. By means of appropriate time cuts, the neutrino search has been restricted to the periods when the acceleration of relativistic jets was taking place at the microquasars under study. The time cuts have been chosen using the information from the X-ray telescopes RXTE/ASM and Swift/BAT, and, in one case, the gamma-ray telescope Fermi/LAT. No statistically significant excess has been observed, thus upper limits on the neutrino fluences have been derived and compared to the predictions by models. Constraints have been put on the ratio of proton to electron luminosity in the jets.